Digital communication between superiors and subordinates in Borneo Export and Import Trading Company (Intercultural communication perspective) - Wijaya, Vionita; Rachmad, Teguh Hidayatul (C-DISC, 2023)
This research aims to find out how to smoothly establish digital communication between supervisors and subordinates who have different cultures and languages in PT Borneo Export and Import Trade Company. PT Borneo Export and Import Trade is a company involved in the food and beverage industry, especially in the swallow's nest health food. This research uses transactional analysis theory to see the extent of communication between superiors and subordinates effectively and uses bureaucratic theory to see the communication patterns that exist between superiors and subordinates at PT Borneo Export and Import Trade. This research uses a qualitative method with a constructivist approach to see the social reality of the case. According to the findings of the study, there are indeed barriers in this intercultural communication, but intercultural communication is successfully carried out by using digital communication, namely using Google Translate application as translation.